A method for preparing starch-based hard carbon negative electrode material, negative electrode material and sodium ion battery
By adding coal powder in the preparation process of starch-based hard carbon negative electrode material, the problem of starch foaming is solved, the compaction density and energy density of the material are improved, and better electrochemical performance is achieved.
Patent Information
- Application Number
- CN202310748266.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-06-21
AI Technical Summary
When mass-producing starch-based hard carbon negative electrode materials, starch is prone to foaming, resulting in unstable material properties and affecting energy density.
By incorporating coal-based materials, especially in the pre-carbonization stage, it helps to build gas channels, absorb excess heat, inhibit starch foaming, and improve the compaction density of the material.
It effectively inhibits the foaming phenomenon of starch during carbonization, improves the compaction and energy density of the material, and improves the electrochemical performance.
Smart Images

Figure CN116768190B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical technology, and more specifically, relates to a preparation method of a starch-based hard carbon negative electrode material, a negative electrode material and a sodium ion battery. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life and environmental protection, and have been widely used in various portable electronic devices and electric vehicles. However, the uneven distribution of lithium resources and the increasing cost restrict its development. Sodium-ion batteries have a similar working principle to lithium-ion batteries and have lower potential costs, and are considered to be a potential substitute for lithium-ion batteries. Carbon materials have the advantages of abundant resources, low cost, non-toxicity and high safety. The feasibility of their sodium storage has been confirmed, and a large number of studies have shown that carbon materials can be ideal sodium storage materials.
[0003] Hard carbon materials are prepared by biomass-based or coal-based carbonization. Biomass-derived hard carbon materials have the advantages of abundant sources, simple preparation, and low price. As negative electrode materials for sodium ion batteries, they have good electrochemical properties. Starch is the most abundant biopolymer in nature. Its special polymerization mode shows that it has the potential of bio-derived carbon. Compared with carbon materials obtained from most animal and plant tissues, starch-based carbon materials are more suitable for the preparation of electrode materials in terms of morphological plasticity, multifunctionality of use, and diversity of treatment methods. During the high-temperature carbonization process, untreated starch will develop into a foamy fluffy structure due to its own structural reasons, and the starch particles will expand and adhere to each other. Therefore, esterification agents are often used in the literature to esterify starch to reduce the foaming phenomenon of starch during carbonization. However, the esterified starch produced by different esterification processes is different. The starch after esterification in some processes does not foam when it is small, but foaming still occurs in the scale-up production. This is because the degree of esterification in some processes is small. During large-scale production, the water vapor increases when the starch is dehydrated, and the temperature inside the starch increases, causing foaming.
[0004] Among hard carbon materials, the compaction density of biomass-based materials produced industrially is much lower than that of traditional graphite due to the characteristics of the raw materials. The compaction density of coal-based hard carbon is 1.1-1.3 g / cm 3 The compacted density of biomass-based hard carbon is generally lower than 1.0 g 5 cm 3 , generally between 0.85 and 1.0 g / cm 3 Therefore, the compaction density of the sodium-based hard carbon anode is also an important indicator of material performance, affecting the final energy density of the material. How to improve the energy density of biomass-based sodium-based hard carbon anode materials is a key direction of research and development.
[0005] For example, the patent application document with Chinese patent application number 202211364293.2 and application publication date of December 30, 2022 discloses a method for preparing starch-based hard carbon negative electrode materials, negative electrode materials and sodium ion batteries. The patent uses linear heating to pretreat starch, with short pretreatment time and low pretreatment temperature, which shortens the production cycle and reduces the production cost of the enterprise; starch is partially or completely esterified with polyhydroxy organic acid or organic anhydride during pretreatment, and starch molecules are esterified to form a spatial network structure, while also releasing part of the water and small molecules contained in the starch, which plays a stabilizing role; the application uses pretreatment, precarbonization and high-temperature sintering, which not only solves the problems of starch foaming and melting during heating, but also improves the yield of starch, and obtains a carbon material with dense structure, high bulk density, small specific surface area and excellent electrochemical performance. However, due to the different types of polyhydroxy organic acids or organic anhydrides, they cannot be completely esterified with starch. During mass production, starch accumulates, internal water vapor is difficult to be discharged, local temperature rises, and unesterified starch is very easy to gelatinize, foam and melt. For such organic acids or organic anhydrides with poor esterification effects, the present invention can solve the problems arising in mass production.
[0006] The patent application document with Chinese patent application number 201510926187.2 and application publication date April 27, 2016 discloses a method for preparing hard carbon materials for lithium-ion battery negative electrodes. The patent uses polyhydroxy alcohol as the hard carbon source, and obtains it through gelatinization, solidification, crushing, grading, and coal tar kneading modification. The compacted density of the hard carbon negative electrode material prepared by the invention method is as high as 1.5g / cc, the reversible capacity is higher than 600mAh / g, and the first efficiency is about 90%. However, in the processing process described in the patent, the starch used is water-soluble starch, which is subjected to gelatinization, solidification, crushing and other steps, which increases the difficulty and cost of operation, and destroys the original particle morphology of the starch. The production process of the present invention is simpler, and the original particle morphology of the starch is guaranteed after carbonization, which is more conducive to the subsequent research on material modification to improve product performance.
[0007] The patent application document with Chinese patent application number 201510708632.8 and application publication date of December 23, 2015 discloses a negative electrode material for sodium ion secondary batteries, a preparation method and use thereof. The patented material is an amorphous carbon-carbon material, which is obtained by high-temperature cracking of coal as the main raw material: coal and hard carbon precursor are used as raw materials, mechanically mixed after adding solvent, dried, and then prepared by crosslinking, curing and cracking under an inert atmosphere. Or coal is used as raw material and cracked under an inert atmosphere. The sodium ion secondary battery using the above material as the negative electrode material has low cost and high working voltage, stable cycle and good safety performance. However, the patent scheme is mainly based on coal, the hard carbon precursor is coated by solvent, and starch still foams under this condition. Since the weight of the example mixture in the patent is only 3g, it is difficult to observe the foaming phenomenon; the use of spray drying will affect the processing cost; the electrochemical performance of the material obtained after carbonization is poor and it is not competitive. This application is mainly based on starch, and the addition of coal powder mainly does not adjust the thermal conductivity process during the pre-carbonization process, has no effect on the starch structure, and the material has excellent electrochemical properties and is more competitive.
[0008] Therefore, in order to solve the problem of starch foaming, it is urgent to seek a method for preparing starch-based hard carbon negative electrode materials to obtain negative electrode materials and sodium ion batteries. Summary of the invention
[0009] 1. Problem to be solved
[0010] The purpose of the present invention is to provide a method for preparing starch-based hard carbon negative electrode materials to solve the problem of starch foaming during the existing batch production of starch-based hard carbon negative electrode materials, and further obtain negative electrode materials and sodium ion batteries.
[0011] 2. Technical solution
[0012] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0013] The present invention prepares a composite hard carbon sodium ion battery negative electrode material with starch and coal as main and secondary materials by adding coal-based materials. Specifically, a preparation method of a starch-based hard carbon negative electrode material comprises the following steps:
[0014] (1) Esterification treatment: The starch and the esterifying agent are mechanically mixed, and the mechanical mixing method is one of VC mixing, fusion, and three-dimensional mixing. The mixed material is placed in a crucible for esterification treatment to obtain an esterified material, wherein the material contains incompletely esterified starch.
[0015] (2) Pre-carbonization treatment: The esterified material is added to coal powder for mechanical mixing. The mechanical mixing method is one of VC mixing, fusion, and three-dimensional mixing. The mixed material is placed in a crucible for pre-carbonization treatment. The main purpose of introducing coal powder is to build a good gas discharge channel inside the starch, which helps to discharge water vapor in time during the starch carbonization process, avoid starch gelatinization, and inhibit foaming. At the same time, coal powder itself has excellent heat resistance and can absorb the heat accumulated inside the starch, control the temperature difference between the inside and outside of the starch, avoid local overheating, and produce local foaming. In terms of performance, coal powder has a higher compaction density than starch-based hard carbon. The blending of coal powder can improve the overall compaction density of the product, which helps to improve the energy density of the product to obtain a better range of applications.
[0016] (3) Crushing: The pre-carbonized material is crushed, and the crushing method is one of air flow crushing, mechanical crushing, and ball milling. The crushing process is mainly to control the particle size of the material. Due to the short-range and disordered structure inside the hard carbon material, a smaller particle size is conducive to the insertion and extraction of sodium with a large atomic radius, thereby improving the electrochemical performance of the material;
[0017] (4) Carbonization treatment: The crushed material is placed in a crucible for carbonization treatment to obtain a starch-based hard carbon negative electrode material.
[0018] Furthermore, the structure of esterifying agents with a high degree of esterification is generally more complex, containing structures such as benzene rings, and the cost is high. The esterifying agents are highly harmful. The present application is directed to low-cost esterifying agents with a low degree of esterification, and the esterifying agents are organic acids or organic anhydrides. The organic acid is a mixture of one or more dibasic organic acids such as maleic acid, glutaric acid, and succinic acid; the organic anhydride is a mixture of one or more anhydrides such as maleic anhydride, glutaric anhydride, and succinic anhydride.
[0019] Furthermore, the weight proportions of starch and esterifying agent are: 70-90 parts of starch, 10-30 parts of esterifying agent; the weight proportions of esterified material and coal powder are: 70-90 parts of esterified material, 10-30 parts of coal powder.
[0020] Furthermore, the D50 of starch is 5-15μm; the particle size of the esterifying agent is 50-400 mesh; and the D50 of the coal powder is 5-10μm. The starch particle size purchased by different manufacturers is different. The starch particle size basically determines the sample particle size in the final product and affects the final electrochemical performance. Reducing the particle size of the esterifying agent is conducive to the full contact between the esterifying agent and the starch, ensuring the complete esterification reaction and affecting the pre-carbonization effect. As a hard carbon precursor, the coal powder itself presents a short-range disordered structure inside. The particle size is controlled within a certain range, which is conducive to the embedding and extraction of sodium ions during the charge and discharge process, and improves the electrochemical performance of the product. At the same time, the coal powder after particle size control can ensure that the distribution of starch particles is more uniform and reasonable, and optimize the exhaust channel. If the coal powder particle size is too small, it can only fill the pores of the starch particles and cannot construct the exhaust channel; if the particle size is too large, the distribution of starch particles cannot be guaranteed, and spherical granular foaming will occur.
[0021] Further,
[0022] The reaction conditions of the esterification treatment are a heating rate of 1 to 5°C for 5 min, an esterification temperature of 70 to 100°C, and a holding time of 2 to 5 h;
[0023] The reaction conditions of the pre-carbonization treatment are: a heating rate of 1 to 3°C 5m55, a pre-carbonization temperature of 200 to 500°C, and a holding time of 2 to 10h; the various process parameters during the pre-carbonization process can control the degree and rate of material dehydration, which is helpful to regulate the specific surface area of the material.
[0024] The reaction conditions of carbonization treatment are: heating rate of 1-3℃5m55, carbonization temperature of 1000-1500℃, and insulation time of 2-5h. The various process parameters of carbonization process can control the degree and rate of volatile matter emission of materials, help control the content of effective ingredients of materials, and have a certain influence on the specific surface area of materials.
[0025] Furthermore, the esterification treatment is carried out in an air atmosphere, and the pre-carbonization treatment and the carbonization treatment are carried out in an inert gas, wherein the inert gas is a mixture of one or more of argon, helium, and nitrogen.
[0026] Furthermore, the D50 of the crushed material is controlled to be 5 to 15 μm.
[0027] The key of the present invention is to provide a method for preparing a starch-based hard carbon negative electrode. By adding coal powder, the direct contact of esterified starch is reduced, the excess heat inside the starch is absorbed and controlled, the foaming phenomenon of starch during the carbonization process is suppressed, and the problems existing in the large-scale production of esterified starch are solved; the addition of coal powder has little effect on the first effect of sample capacity, while increasing the compaction density of the starch sample and improving the volume energy density of the product.
[0028] A starch-based hard carbon negative electrode material is prepared by the above-mentioned preparation method.
[0029] A sodium ion battery comprises a negative electrode, wherein the negative electrode comprises the starch-based hard carbon negative electrode material as described above.
[0030] 3. Beneficial effects
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention solves the problem of easy foaming of esterified starch during the pre-carbonization process by adding coal powder in the pre-carbonization stage. The addition of coal powder helps to reduce the contact area of starch particles, which is beneficial to the construction of gas channels, and further facilitates the release of water vapor during the pre-carbonization process; and the added coal powder can absorb excess heat and construct a heat conduction channel to avoid local overheating inside the starch, thereby inhibiting the foaming problem of starch during the carbonization process. On the other hand, the addition of coal powder can also increase the compaction density of starch-based hard carbon materials, which helps to increase the volume energy density of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a diagram of the pre-carbonization result in Example 1;
[0034] Figure 2 This is the pre-carbonization result diagram in Comparative Example 2;
[0035] Figure 3 This is the carbonized XRD pattern of starch in Comparative Example 1;
[0036] Figure 4 The XRD diagram of coal powder carbonization in Comparative Example 3;
[0037] Figure 5 This is the XRD pattern of starch + coal in Example 1;
[0038] Figure 6 These are SEM images (a. SEM image of carbonized starch in Comparative Example 1; b. SEM image of carbonized coal powder in Comparative Example 3; c. SEM image of carbonized starch + coal in Example 1). DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with specific embodiments.
[0040] Example 1
[0041] (1) Raw material mixing: Starch (D50 is 9 μm) and maleic anhydride (100 mesh) are mixed with VC at a mass ratio of 5:1.
[0042] (2) Esterification: The mixed materials are placed in a crucible and esterified in an air atmosphere. The esterification process is as follows: a heating rate of 5°C 5 min 55, an esterification temperature of 80°C, and a holding time of 3 h.
[0043] (3) Mixing: 2500 g of the esterified material was mixed with coal (D50: 8 μm) at a mass ratio of 4:1 and VC was added.
[0044] (4) Pre-carbonization: The mixed materials are placed in a crucible and pre-carbonized in a nitrogen atmosphere. The pre-carbonization process is as follows: a heating rate of 2°C 5 min 55 and a heat preservation of 300°C for 3 hours.
[0045] (5) Crushing: ball mill the pre-carbonized material to control the particle size (D50 is 8 μm)
[0046] (6) Carbonization: The crushed material is placed in a crucible and carbonized in a nitrogen atmosphere. The carbonization process is as follows: a heating rate of 2°C 5 min 55, a carbonization temperature of 1300°C, and a holding time of 3 h.
[0047] The final negative electrode material has a capacity of 292 mAh / g, a first efficiency of 86.6%, and a compaction density of 0.97 g / cm 3 .
[0048] Example 2
[0049] (1) Raw material mixing: Starch (D50 is 9 μm) and glutaric anhydride (100 mesh) are mixed with VC at a mass ratio of 5:1.
[0050] (2) Esterification: The mixed materials are placed in a crucible and esterified in an air atmosphere. The esterification process is as follows: a heating rate of 5°C 5 min 55, an esterification temperature of 80°C, and a holding time of 3 h.
[0051] (3) Mixing: 2500 g of the esterified material was mixed with coal (D50: 8 μm) at a mass ratio of 7:3 by VC.
[0052] (4) Pre-carbonization: The mixed materials are placed in a crucible and pre-carbonized in a nitrogen atmosphere. The pre-carbonization process is as follows: a heating rate of 1°C 5 min 55 and a heat preservation of 400°C for 3 hours.
[0053] (5) Crushing: Mechanically crush the pre-carbonized material to control the particle size (D50 is 8 μm)
[0054] (6) Carbonization: The crushed material is placed in a crucible and carbonized in a nitrogen atmosphere. The carbonization process is as follows: a heating rate of 2°C 5 min 55, a carbonization temperature of 1100°C, and a holding time of 3 h.
[0055] The final lithium-ion negative electrode material has a capacity of 275 mAh / g, a first efficiency of 84.4%, and a compaction density of 1.02 g / cm 3 .
[0056] Example 3
[0057] (1) Raw material mixing: Starch (D50 is 9 μm) and succinic anhydride (100 mesh) are mixed with VC in a mass ratio of 5:1.
[0058] (2) Esterification: The mixed materials are placed in a crucible and esterified in an air atmosphere. The esterification process is as follows: a heating rate of 5°C 5 min 55, an esterification temperature of 80°C, and a holding time of 3 h.
[0059] (3) Mixing: 2500 g of the esterified material was mixed with coal (D50: 8 μm) at a mass ratio of 7:3 by VC.
[0060] (4) Pre-carbonization: The mixed materials are placed in a crucible and pre-carbonized in a nitrogen atmosphere. The pre-carbonization process is as follows: a heating rate of 3°C 5 min 55, and a heat preservation temperature of 450°C for 3 h.
[0061] (5) Crushing: The pre-carbonized material is subjected to air flow crushing to control the particle size (D50 is 8 μm)
[0062] (6) Carbonization: The crushed material is placed in a crucible and carbonized in a nitrogen atmosphere. The carbonization process is as follows: a heating rate of 2°C 5 min 55, a carbonization temperature of 1300°C, and a holding time of 3 h.
[0063] The final negative electrode material has a capacity of 287 mAh / g, a first efficiency of 85.8%, and a compaction density of 1.05 g / cm 3 .
[0064] Example 4
[0065] (1) Raw material mixing: Starch (D50 is 9 μm) and maleic acid (100 mesh) are mixed with VC at a mass ratio of 5:1.
[0066] (2) Esterification: The mixed materials are placed in a crucible and esterified in an air atmosphere. The esterification process is as follows: a heating rate of 5°C 5 min 55, an esterification temperature of 80°C, and a holding time of 3 h.
[0067] (3) Mixing: 2500 g of the esterified material was mixed with coal (D50: 8 μm) at a mass ratio of 4:1 and VC was added.
[0068] (4) Pre-carbonization: The mixed materials are placed in a crucible and pre-carbonized in a nitrogen atmosphere. The pre-carbonization process is as follows: a heating rate of 2°C 5 min 55 and a heat preservation of 500°C for 3 hours.
[0069] (5) Crushing: ball mill the pre-carbonized material to control the particle size (D50 is 8 μm)
[0070] (6) Carbonization: The crushed material is placed in a crucible and carbonized in a nitrogen atmosphere. The carbonization process is as follows: a heating rate of 2°C 5 min 55, a carbonization temperature of 1500°C, and a holding time of 3 h.
[0071] The final negative electrode material has a capacity of 287 mAh / g, a first efficiency of 95.4%, and a compaction density of 0.96 g / cm 3 .
[0072] Comparative Example 1
[0073] (1) Raw material mixing: Starch (D50 is 9 μm) and maleic anhydride (100 mesh) are mixed with VC at a mass ratio of 5:1.
[0074] (2) Esterification: The mixed materials are placed in a crucible and esterified in an air atmosphere. The esterification process is as follows: a heating rate of 5°C 5 min 55, an esterification temperature of 80°C, and a holding time of 3 h.
[0075] (3) Pre-carbonization: 50 g of the esterified material was placed in a crucible and pre-carbonized in a nitrogen atmosphere. The pre-carbonization process was as follows: a heating rate of 2°C 5 min 55 and a heat preservation temperature of 300°C for 3 h.
[0076] (4) Crushing: The pre-carbonized material is subjected to air flow crushing to control the particle size (D50 is 8 μm)
[0077] (5) Carbonization: The crushed material is placed in a crucible and carbonized in a nitrogen atmosphere. The carbonization process is as follows: a heating rate of 2°C 5 min 55, a carbonization temperature of 1300°C, and a holding time of 3 h.
[0078] The capacity of starch carbonization material is 300mAh / g, the first efficiency is 89.3%, and the compaction density is 0.9g / cm 3 .
[0079] Comparative Example 2
[0080] (1) Raw material mixing: Starch (D50 is 9 μm) and maleic anhydride (100 mesh) are mixed with VC at a mass ratio of 5:1.
[0081] (2) Esterification: The mixed materials are placed in a crucible and esterified in an air atmosphere. The esterification process is as follows: a heating rate of 5°C 5 min 55, an esterification temperature of 80°C, and a holding time of 3 h.
[0082] (3) Pre-carbonization: 2500 g of the esterified material was placed in a crucible and pre-carbonized in a nitrogen atmosphere. The pre-carbonization process was as follows: a heating rate of 2°C 5 min 55 and a heat preservation temperature of 300°C for 3 h.
[0083] Starch foaming occurs.
[0084] Comparative Example 3
[0085] (1) Crushing: The coal powder raw material is subjected to air flow crushing to control the particle size (D50 is 8μm)
[0086] (2) Carbonization: The crushed material is placed in a crucible and carbonized in a nitrogen atmosphere. The carbonization process is as follows: a heating rate of 2°C 5 min 55, a carbonization temperature of 1300°C, and a holding time of 3 h.
[0087] The capacity of coal powder after carbonization is 260mAh / g, the first efficiency is 82.3%, and the compaction density is 1.19g / cm 3 .
[0088] Comparative Example 4
[0089] (1) Mixing: Unesterified starch raw material and coal (D50 is 8 μm) were mixed by VC at a mass ratio of 4:1, 3:1, and 2:1, respectively.
[0090] (2) Pre-carbonization: 500 g of the mixed material was placed in a crucible and pre-carbonized in a nitrogen atmosphere. The pre-carbonization process was as follows: a heating rate of 2°C 5 min 55 and a heat preservation temperature of 300°C for 3 h.
[0091] Conclusion: Foaming occurs at different mixing ratios.
[0092] Result analysis:
[0093] (1) The pre-carbonization results of Example 1 and Comparative Example 2 are shown in Figures 1 and 2. Figure 1 and Figure 2 As shown, in which Example 1 did not produce foaming when coal powder was added, while Comparative Example 2 produced foaming of esterified starch; Comparative Examples 1 and 2 show that esterified starch did not produce foaming when used in small amounts, but produced foaming when used in batches;
[0094] (2) Comparative Example 4 shows that after the unesterified starch is mixed with the coal powder, foaming still occurs, indicating that there is a synergistic effect between the starch, the esterifying agent and the coal powder, which ensures the stability of the material in mass production;
[0095] (3) Comparative Example 1 ( Figure 3 ), Comparative Example 3( Figure 4 ) and Example 1 ( Figure 5) was subjected to XRD, and the results showed that the peak shape and peak position of starch-based hard carbon and coal powder can be observed on the XRD spectrum of the product after mixing with coal powder; and then respectively compared with Example 1 ( Figure 6 a), Comparative Example 3 ( Figure 6 b) and Example 1 ( Figure 6 The carbonized product in (c) was subjected to SEM analysis, wherein (c) shows that after the coal powder was mixed, the particles were not bonded, the coal powder did not react with the starch, and did not affect the structure of the starch particles;
[0096] (4) The negative electrode material performance table of Examples 1 to 4 and Comparative Examples 1 to 4 shows that the final carbonization temperature has an impact on the material properties, and a suitable carbonization temperature is conducive to the release of material properties. The addition of coal powder will affect the material properties, but the impact is small, and the material compaction density is significantly improved, which is beneficial to improving the energy density of the material.
[0097] The examples described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a starch-based hard carbon negative electrode material, characterized in that: The steps are: starch and an esterifying agent are mixed for esterification treatment, coal powder is added and mixed, and then pre-carbonization treatment is performed, the material after pre-carbonization treatment is crushed, and finally carbonization treatment is performed to obtain a starch-based hard carbon negative electrode material; wherein the mass fractions of starch and the esterifying agent are: 70-90 parts of starch and 10-30 parts of the esterifying agent; the mass fractions of the material after esterification treatment and coal powder are: 70-90 parts of the material after esterification treatment and 10-30 parts of coal powder; The reaction conditions of the esterification treatment are a heating rate of 1 to 5°C / min, an esterification temperature of 70 to 100°C, and a holding time of 2 to 5h; The reaction conditions of the pre-carbonization treatment are: a heating rate of 1 to 3°C / min, a pre-carbonization temperature of 200 to 500°C, and a holding time of 2 to 10 hours; The reaction conditions of the carbonization treatment are: a heating rate of 1 to 3°C / min, a carbonization temperature of 1000 to 1500°C, and a heat preservation time of 2 to 5h.
2. The method for preparing a starch-based hard carbon negative electrode material according to claim 1, characterized in that: The esterifying agent is an organic acid or an organic acid anhydride.
3. The method for preparing a starch-based hard carbon negative electrode material according to claim 2, characterized in that: The organic acid is a mixture of one or more dibasic organic acids selected from maleic acid, glutaric acid and succinic acid; the organic anhydride is a mixture of one or more dibasic organic acids selected from maleic anhydride, glutaric anhydride and succinic anhydride.
4. The method for preparing a starch-based hard carbon negative electrode material according to claim 1, characterized in that: The D50 of starch is 5-15 μm; the particle size of the esterifying agent is 50-400 mesh; and the D50 of the coal powder is 5-10 μm.
5. The method for preparing a starch-based hard carbon negative electrode material according to claim 1, characterized in that: The esterification treatment is carried out in an air atmosphere, and the pre-carbonization treatment and the carbonization treatment are carried out in an inert gas, wherein the inert gas is a mixture of one or more of argon, helium, and nitrogen.
6. The method for preparing a starch-based hard carbon negative electrode material according to claim 1, characterized in that: The D50 of the crushed material is controlled to be 5-15μm.
7. A starch-based hard carbon negative electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. A sodium ion battery, characterized in that: It comprises a negative electrode, wherein the negative electrode comprises the starch-based hard carbon negative electrode material as claimed in claim 7.
Citation Information
Patent Citations
Sodion secondary battery negative electrode material and preparing method and application thereof
CN105185997A
A method for preparing hard carbon material for lithium-ion battery anodes
CN105529443B
Preparation method of starch-based hard carbon negative electrode material, negative electrode material and sodium ion battery
CN115536002A